Penilaian Kesesuaian Dan Standar Usaha Restoran Berisiko Menengah Rendah Di Dua Tiga Coffee House - Christin, Juan; Prayogi, Budi (Jurnal Akademi Pariwisata Medan, 2024)
Conformity assessment can be interpreted as an activity to assess whether goods, services, systems, processes, or personnel have met the requirements (National Standardization Agency, 2023). Conformity assessment of business standards is very important to be carried out, in order to minimize the risks that will occur. To regulate conformity assessments, especially to carry out risk management functions, the Ministry of Tourism and Creative Economy issued the Minister of Tourism and Creative Economy Regulation No. 4/2021 concerning the conformity assessment and standards of low-medium risk restaurant businesses. The purpose of this assessment is (1) to determine the conformity assessment and standards of low-risk restaurant businesses of two three coffee houses, (2) to determine the design of facilities and landscapes in two three coffee houses in accordance with the conformity assessment and standards of low-risk restaurant businesses. This study uses a qualitative method. The primary data source obtained from this study was to provide several questions regarding the management of two three coffee houses. The data collection techniques used were interviews, observations and purposive sampling. The results of this study are (1) Two three coffee houses do not yet have a Certificate of Hygiene Sanitation as a special requirement for the business, the lack of business facilities such as appropriate work rooms, clean water installations, separate waste management and waste disposal installations. The human resources organizational structure of the two three coffee houses is quite good, only the employees do not wear uniforms that include the logo and the management of the two three coffee houses does not yet have a SOP document for work implementation and business management that has not been documented. (2) For the design and landscape in the two three coffee houses, the author designed one room consisting of an administration room and a manager's room. Other added facilities are women's and men's toilets, two wash basins, organic and non-organic trash bins, a rooftop on the 2nd floor, and several other ornamental plants.